Endocrine Disruption: Structural Interactions of Androgen Receptor against Di(2-ethylhexyl) Phthalate and Its Metabolites - Mohd Amin Beg; Ishfaq Ahmad Sheikh (Toxics, 2020)
Diethylhexyl phthalate (DEHP) is a commonly used plasticizer in the manufacture of polyvinyl chloride plastics for household and commercial use. DEHP is a ubiquitous ecocontaminant and causes developmental and reproductive problems in children and adults. After exposure, DEHP is metabolized by endogenous hydrolysis and oxidation into the primary metabolite, mono-(2-ethylhexyl) phthalate (MEHP), and the secondary metabolites, mono-(2-ethyl-5-hydroxhexyl)phthalate (5-OH-MEHP), mono-(2-ethyl-5-oxohexyl) phthalate (5-oxo-MEHP), mono-(2-ethyl-5-carboxypentyl) phthalate (5-cx-MEPP), and mono-[(2-carboxymethyl)hexyl] phthalate (2-cx-MMHP). Very few studies have been reported on the adverse effects of DEHP metabolites, and the available information indicates that the metabolites might also be equally or more active as compared to the parent compound. In the present study, induced fit docking was used for structural binding characterization of the above five DEHP metabolites with androgen receptor (AR) to predict the potential endocrine-disrupting effects of these metabolites in AR signaling. All the DEHP metabolites interacted with the ligand-binding pocket of AR forming amino-acid residue interactions, hydrogen bonding, and pi-pi interactions. The binding energy of DEHP with AR was similar to that of native ligand testosterone. The amino-acid residue interactions of DEHP metabolites had 91–100% similarity compared to that of testosterone. In addition, all the DEHP metabolites and testosterone showed a common hydrogen bonding interaction with amino-acid Arg-752 of AR. Taken together, the structural binding data in the present study suggested the potential for DEHP metabolites to disrupt AR signaling, which may lead to androgen-related reproductive dysfunction.